THE EFFECTIVENESS OF ZAKAT, INFAQ, AND SHODAQOH IN ALLEVIATING POVERTY IN INDONESIA: USING BASIC NEEDS DEFICIENCY INDEX - Lintang Titian Purbasari; Raditya Sukmana; Ririn Tri Ratnasari (Universitas Airlangga, 2020)
This study aims to examine the role of zakat, infaq and shodaqoh in alleviating poverty in Indonesia for the period 2015-2017. The methodology of this study uses a qualitative approach and the BNDI index is formulated to measure the shortcomings and effectiveness of zakat, infaq and shodaqoh in alleviating poverty. The results obtained from BNDI calculations have been able to explain the effectiveness of zakat, infaq and shodaqoh in alleviating poverty in Indonesia. The calculation results that show large value or close to the value of 1 explains that zakat, infaq, shodaqoh distributed by the BAZNAS Center are not effective in reducing poverty in Indonesia. In the results of this study, there are several provinces with the highest BNDI and the lowest BNDI. This study is expected to be used for policymakers to increase the effectiveness of zakat, infaq, and shodaqoh in alleviating poverty.Keywords: Indonesia, Zakat, Infaq, Shodaqoh, Poverty, Basic Needs Deficiency Index (BNDI).REFFERENCE AA. Anwar Prabu Mangkunegara. (2013). Manajemen sumber daya manusia perusahaan. Bandung: Remaja Rosdakarya.Atabik, Ahmad. 2015. Peranan zakat dalam pengentasan kemiskinan. Jurnal Zakat dan Wakaf, 2(2), 339-361. Chaniago, Siti Aminah. (2015). Pemberdayaan zakat dalam mengentaskan kemiskinan. Jurnal Hukum Islam, 13(1), 47-56.Didin, Hafidhuddin dan Hendri Tanjung. (2003). Manajemen syariah dalam praktik. Jakarta: Gema Insani Press.Etzioni, A. (1964). Modern organizations. Englewood Cliffs: Prentice Hall.Johnston, Melissa P. (2014). Secondary Data Analysis: A Method that which a Time Has Come. Quantitative and Qualitative Methods in Library, 3(3), 619-626.Kementerian Agama Republik Indonesia Tahun. (2016). Alquran dan terjemahan. Bandung: CV Media Fitrah Rabbani.Kuncoro, Mudrajad. (1997). Ekonomi pembangunan, teori masalah dan kebijakan. Yogyakarta: UPP AMP YKPN.Kurniawan, Agung. (2005). Transformasi pelayanan publik. Yogyakarta: Pembaharuan.Lukman Raimi Ashok Patel Ismail Adelopo . (2014). Corporate social responsibility, Waqf system and Zakat system as faith-based model for poverty reduction. World Journal of Entrepreneurship, Management and Sustainable Development, 10(3), 228-242.Muhidin, Sambas Ali. (2009). Konsep efektivitas pembelajaran. Diambil dari http://sambasalim.com/pendidikan/konsep-efektivitas-pembelajaran.htmlMahmudi. (2005). Manajemen kinerja sektor publik. Yogyakarta: UPP AMP YKPN.Mukhadis, Amat. (2013). Evaluasi program pembelajaran bidang teknologi (terminologi, prosedur pengembangan program dan instrumen). Malang: Bayumedia Publishing.Pius A. Partanto dan M. Dahlan al-Barry. (2002). Kamus ilmiah populer. Surabaya: Arkola.Qal‟ahji, Muhammad Rawwas. (1999). Ensiklopedi fiqh Umar ibn al-Khattab. Jakarta: PT. Raja Grafindo Persada.Ryandono, Muhammad Nafik Hadi. (2008). Ekonomi ZISWAQ (zakat, infak, shodaqoh, dan wakaf). Surabaya: IFDI dan Cenforis.Sartika, Cica, M. Yani Balaka, dan Wali Aya Rumbia. (2016). Studi faktor-faktor penyebab kemiskinan masyarakat desa lohia kecamatan lohia kabupaten Muna. Jurnal Ekonomi, 1(1), 106-118.Sedarmayanti. (2009). Sumber daya manusia dan produktivitas kerja. Bandung: Mandar Maju.Sugiyono. (2016). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: PT Alfabet.Todaro, Michael P dan Stephen C. Smith. (2008). Pembangunan ekonomi. Edisi kesembilan. Jakarta: Erlangga.Yin, Robert K. (2015). Studi kasus desain & metode. Jakarta: Rajawali Press.Yin, R.K. (2014). Case study research. Design and methods, 5th ed. London, Thousand Oaks: Sage Publications.www.bps.go.idwww.baznas.go.idwww.humassulbarprov.idwww.sp2010.go.id